Carbon nanofibers obtained from electrospinning process - De Oliveira, Juliana Bovi [UNESP] (2018)
In recent years, reinforcements consisting of carbon nanostructures, such as carbon nanotubes, fullerenes, graphenes, and carbon nanofibers have received significant attention due mainly to their chemical inertness and good mechanical, electrical and thermal properties. Since carbon nanofibers comprise a continuous reinforcing with high specific surface area, associated with the fact that they can be obtained at a low cost and in a large amount, they have shown to be advantageous compared to traditional carbon nanotubes. The main objective of this work is the processing of carbon nanofibers, using polyacrylonitrile (PAN) as a precursor, obtained by the electrospinning process via polymer solution, with subsequent use for airspace applications as reinforcement in polymer composites. In this work, firstly PAN nanofibers were produced by electrospinning with diameters in the range of (375 ±85) nm, using a dimethylformamide solution. Using a furnace, the PAN nanofiber was converted into carbon nanofiber. Morphologies and structures of PAN and carbon nanofibers were investigated by scanning electron microscopy, Raman Spectroscopy, thermogravimetric analyses and differential scanning calorimeter. The resulting residual weight after carbonization was approximately 38% in weight, with a diameters reduction of 50%, and the same showed a carbon yield of 25%. From the analysis of the crystalline structure of the carbonized material, it was found that the material presented a disordered structure.